The Role of Membrane-Based Technologies in Environmental Treatment and Reuse of Produced Water - Zolghadr, Ehsan; Firouzjaei, Mostafa Dadashi; Amouzandeh, Ghoncheh; LeClair, Patrick; Elliott, Mark (Frontiers in Environmental Science, 2021)
Produced water (PW) generation has been increasing recently due to the expansion of fossil fuel extraction and the aging of oil wells worldwide and especially in the United States (US). The adverse health risks, seismicity, and environmental impacts associated with PW have become a challenging concern. Therefore, there is increased demand for improved PW treatment and reuse management options. There are multiple methods for treating PW; this article focuses on treatment through membrane filtration. Moreover, this mini review aims to summarize statistics on PW abundance, trends in PW generation over time, to briefly call attention to health-related issues, highlight some treatment challenges, and mention potential purposes for reuse with an emphasis on the US, the largest generator of PW worldwide.